Research on Full-Cycle Teaching Reform of IoT Cloud Platform Application Development Driven by CDIO Model - He, Yantao; Huang, Pengteng; Yu, Liang; Zhang, Xiaochen; Zhou, Lanping (Education Insights, 2025)
This research, guided by the Conceive-Design-Implement-Operate (CDIO) model, emphasizes full-cycle teaching reform and practice within the context of an Internet of Things (IoT) cloud platform application development. The primary focus is on enhancing students’ engineering practice capabilities, deeply exploring and implementing the entire "ideation-design-implementation-operation" process in effective teaching methodologies. Through this research, our goal is to fully incorporate CDIO’s project-driven concept into professional IoT teaching. This approach enables students to master a comprehensive skill set, ranging from demand analysis to system operation and maintenance, within real project scenarios. Consequently, it enhances their ability to tackle complex engineering problems.